Ethnomathematics in Ulos Abit Godang of South Tapanuli, North Sumatra - Murniati, Murniati; Ginting, Siti Salamah Br (Indonesian Journal of Science and Mathematics Education, 2023)
This research explores ethnomathematics, particularly the relationship between geographical culture and the use of mathematics, focusing on Ulos Abit Godang from South Tapanuli, North Sumatra. As a cultural heritage object, Ulos Abit Godang provides a unique context for analyzing the correlation between mathematical principles and local culture. A qualitative descriptive methodology with ethnographic techniques was adopted to understand the interaction between mathematical concepts and cultural context. The findings reveal a connection between the ideas of set theory and geometric transformation in the Ulos Abit Godang culture. Thus, Ulos Abit Godang of South Tapanuli holds significant ethnomathematical elements, linking cultural heritage to mathematical concepts. These insights offer valuable educational contributions, enriching ethnomathematical methods in teaching mathematics to enhance student creativity and engagement. Future research is suggested to develop similar studies on other cultural artefacts in Indonesia and integrate them into the mathematics education curriculum to enrich student learning experiences.